Status Hukum Anak Angkat dan Pemeliharaannya Pasca Perceraian Orang Tua Angkat - Karin Dwi Ramadhina; Siti Nurul Intan Sari Dalimunthe (Jurnal USM Law Review)
This study aims to determine the status and responsibility of maintaining adopted children after divorce between adoptive parents. Due to the discussion of the topic of the status and responsibility of the maintenance of adopted children, there has been no discussion that has a focus on the rights of adopted children. The divorce of the child's adoptive parents creates uncertainty for the child regarding the existing legal status, not infrequently the perception among the community about the position of the adopted child and the condition of the adopted child who is a child who is maintained and considered like a legitimate child results in the fulfillment of all maintenance for the adopted child in terms of maintenance to provide welfare and protection of the adopted child. The research method used is normative juridical with a statutory approach and a conceptual approach. The results of this study are adopted children whose adoptive parents divorce will not change the legal status of the adopted child towards both adoptive parents and Child Maintenance and Protection becomes an obligation of these parents to be responsible, maintain, and prioritize the rights of adopted children even though they are divorced in accordance with several existing laws and regulations and forms of division in fulfilling maintenance obligations Basically, it does not have special provisions because the most important thing is to prioritize the welfare of the child through the maintenance of the child until the child has grown up.